Prognostic Impact of Cytogenetic Abnormalities in Multiple Myeloma: A Retrospective Analysis of 229 Patients. Issue 19 (May 2016) - Jian, Yuan; Chen, Xiaolei; Zhou, Huixing; Zhu, Wanqiu; Liu, Nian; Geng, Chuanying; Chen, Wenming
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The identification of specific cytogenetic abnormalities by interphase fluorescence in situ hybridization (i-FISH) has become a routine procedure for prognostic stratification of multiple myeloma (MM) patients. In this study, the prognostic significance of cytogenetic abnormalities detected by interphase fluorescence in situ hybridization (iFISH) in 229 newly diagnosed multiple myeloma patients was retrospectively analyzed. Results showed that del (17p), t(4;14), and 1q21 gain were adverse predictors of progression-free survival (PFS). Patients who carried these cytogenetic abnormalities were more likely to have more adverse biological parameters and lower response rate. Multivariate analysis showed that del (17p), t(4;14), and 1q21 gain were statistically independent predictors of PFS, whereas del (17p) was also adverse predictor of overall survival. Multiple coexisting cytogenetic abnormalities also had a negative correlation with PFS. Bortezomib-based therapy could improve the rate and depth of response in patients with t(4;14) translocation and 1q21 gain. Autologous stem cell transplantation could improve, but not overcome the adverse prognostic effect of high-risk cytogenetic abnormalities. These results demonstrate that MM patients with iFISH abnormalities, especially del (17p), are more likely to have a poor prognosis.